Legitimacy at the ‘Margins’: Promotional Strategies in the Canadian For-Profit College Sector - Pizarro Milian, Roger (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2018)
Conventional scholarship within the sociology of education and organizations posits that schools achieve legitimacy by virtue of conforming to normative standards, abiding by government regulations and mimicking the forms of successful peers. Through this study, an examination of a sample of 751 Canadian for-profit colleges (FPCs) is performed, revealing the presence of an alternative logic. Rather than conformity, organizations within this sector engage in niche-seeking behaviour, using promotional materials to carve out unconventional identities. They do so by directly drawing on symbolic resources and affiliations from the industrial sectors which they service. These findings are interpreted through the prism of contemporary theorizing within organizational sociology.